Evaluation of Guiera senegalenses on Prevention of Type 2 Diabetes Among Sudanese Adult Patients - Mohammed, Aida H; Mirghani, Mohamed Elwathig Saeed; Elnour, Ahmed Adam Hassan M.; Abdelbaset, M (IOP Publishing, 2020)
Guiera senegalensis (GS) reflects the reduced glucose exposure of erythrocytes over a preceding time frame proportional to erythrocyte survival. GS is thus an anti-diabetic function of the glucose-time curve, an educationally useful concept to aid teaching and clinical judgment. Sixty-one newly diagnosed patients with an average age of 48.2 years and a weight of 64.9 kg have participated in the study. Participants were significantly different in their educational, socioeconomic levels, and most of them have no family history of diabetes. To evaluate the hypoglycemic effect of GS, the patients were divided into four groups (G1, G2, G3, and G4) and treated with four different doses of the aqueous extract of the herb ( 0.5, 1, 1.5 and 2 Oz of GS boiled for 10 minutes in 0.5-liter water). The experiment has lasted for five days for each group, and the blood glucose level of the patients was checked using GOD–POD method, at fasting (FBS), and following two hours after the breakfast (RBS). Another group of 30 patients (control) received Douniel drug (5mg/day/person) instead of the GS herb extract and checked for glucose level with the same procedure mentioned above. The results revealed that blood glucose level (mg/dl) for all patients lowered by 9% after every 24 hours of the treatment and by 35% at the end of the treatment. The average fasting and random blood glucose levels were significantly (P<0.001) reduced from 326.21 and 322.95 mg/dl at the start of the treatment to 213.57 and 202.87 mg/dl sequentially at the end of the treatment. The herb significantly (P<0.001) reduced the blood glucose levels, however, with negligible side effects (vomiting on two patients of group G4). Similar hypoglycemic effects on random blood sugar for both the herb extract and Daniel drugs noticed. However, the average fasting blood glucose level of patients treated with herb extract (266.21 mg/dl) was significantly (P<0.001) lower than that of patients treated with the Daniel drug (280.47 mg/dl). Accordingly, the action of this herb may be similar to that of Douniel drug. However, it might have more prolonged action than Douniel. The study strongly recommends GS as a potential herb for the treatment of type II diabetes.